Development of Community Character Values in the Sragen Region through Karate Martial Arts Development Based on Character Education - Afifan Yulfadinata; Aghus Sifaq; Nur Ahmad Arief; Riska Susanti (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2026)
This community service program aims to develop character values in the Sragen community through karate martial arts coaching based on character education. The program addresses the challenges faced by the community in maintaining positive character values amidst the influence of globalization, social media negative impacts, and shifting traditional values. Using a Community-Based Research (CBR) approach, this program involved the recruitment and training of karate coaches, socialization to the community, structured training programs integrating character values, and regular monitoring and evaluation. The program was implemented over eight months (March–October 2025) in Sragen, Central Java, targeting youth, students, and local communities. The results showed significant improvements in discipline (from low-moderate to high), responsibility (from moderate to high), sportsmanship (from moderate to high), hard work (from moderate to high), and social respect (from low to moderate-high). Behavioral changes identified included increased time discipline and commitment, decreased aggressive behavior and conflicts, establishment of mutual respect and cooperation culture, and emergence of young leaders. The program produced a character-based karate training model, video documentation, media publications, and policy recommendations. This program proves effective in building community character through karate and has the potential to be replicated in other regions.